Multi-Criteria Frameworks to Improve Evaluation of the Effectiveness of Environmental Governance in the Amazon - Morales-Giner, Pilar; Speranza, Martina Laura; Arteaga, Marliz; Baudoin Farah, Andrea; Ferreira da Fonseca Junior, Sinomar; García Villacorta, Angélica; Rosero Peña, Martha; Perz, Stephen (Frontiers in Forests and Global Change, 2021)
In the Amazon, environmental governance (EG) is an important multi-stakeholder approach to the sustainable management of natural resources. There is by now a large theoretical literature on the many requirements for effective EG. There is also an extensive empirical literature on EG in the Amazon. While empirical work in the Amazon has advanced our understanding of EG, it also has important limitations. There remains a need to unpack the many requirements for effective EG in order to identify violations of particular criteria to explain cases where EG is ineffective. There is also a need for multi-case comparative analyses of EG across diverse parts of the Amazon in order to identify common explanations for ineffective EG. We therefore review multi-criteria frameworks for the evaluation of EG, noting their contributions and differences. We then briefly discuss five study cases in the Amazon, in order to identify common explanations for ineffective EG. We suggest that identification of violations of specific criteria for effective EG can guide targeted conservation action in a specific case. By extension, identification of common criteria violated across cases can provide a basis for broader conservation strategy to improve EG.